Rwanda : 2010 Article IV Consultation and First Review Under the Policy Support Instrument-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Satisfactory implementation of the economic program supported by the Policy Support Instrument has helped Rwanda during the global economic downturn. The program focuses on maintaining a sustainable fiscal position; strengthening monetary and exchange rate policies; and supporting growth with structural reforms to diversify the export base and improve the business environment. The authorities are committed to assess the inflation to safeguard the gains made in macroeconomic stability that currently underpin the economic recovery. Executive Directors emphasized the need to maintain macroeconomic stability to achieve sustainable growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet